Analisis Kinerja Keuangan Badan Usaha Milik Negara (BUMN) Se-Kota Palembang - Muhammad Ichsan Siregar; Afriyadi Cahyadi; Alghifari Mahdi Igamo; Nurdiawansyah Nurdiawansyah; Abdullah Saggaf (Politeknik Ganesha Medan, 2022)
This study measures the financial performance of State-Owned Enterprises (BUMN) throughout the city of Palembang from 2014-2018 using profitability ratios and liquidity ratios. The phenomenon that occurred in one of the State-Owned Enterprises (BUMN) in the city of Palembang in 2019 experienced a decrease in profit compared to the previous year. The type of research conducted in this study uses quantitative research in the form of financial reports. The approach in this study uses a descriptive approach. The types and sources of data used to support the discussion carried out in this study are secondary data. Secondary data obtained and collected by researchers related to financial statements. The population in this study were all State-Owned Enterprises (BUMN). The sample in this study was selected using the purposive sampling method of State-Owned Enterprises throughout the city of Palembang such as PT. Pupuk Sriwidjaja (Persero) and PT. Semen Baturaja Tbk (Persero). The results obtained after analyzing the financial performance of two State-Owned Enterprises (BUMN) from 2014-2018 from PT Pupuk Sriwidjaja (Persero) and PT. Semen Baturaja Tbk (Persero) showed poor results in terms of profitability and liquidity ratios. The profitability ratio as measured by the profit margin ratio, Return on Assets (ROA) and Return on Equity (ROE) indicates a decline in financial performance for five years. The liquidity ratio as measured by the quick and current ratio shows a decline in financial performance from 2014-2017. It was only in 2018 that the fast and smooth ratio showed an increasing graph.